The Strategy Of Qur'an Teachers In Instilling A Love For The Qur'an Among Teenagers At Mussallah Baitul Karimaah, Gg. Sidorukun, Klambir Lima Kebun, Hamparan Perak District, Deli Serdang Regency - Hajar, Ibnu; Ismaraidha, Ismaraidha (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
This study examines the strategies used by Qur'an teachers at Mussallah Baitul Karimaah, Gang Sidorukun, Klambir Lima Kebun, Hamparan Perak District, Deli Serdang Regency, in instilling a love for the Qur'an among teenagers. The background of this research is the low interest of teenagers in Qur'an learning activities and the limited time often faced in deepening religious knowledge. This study employs a descriptive qualitative approach to explore the methods implemented by the Qur'an teachers, including interactive learning, personal approaches, and the instillation of moral and spiritual values through Qur'anic verses relevant to teenagers' lives. The findings indicate that strategies such as Personal Approaches, Motivation-Based Learning, Qur'an Memorization Programs, and Emotional Approaches through group activities were effective. Supporting factors include parental and community support, adequate facilities, and the dedication of Qur'an teachers. Hindering factors include technological and social media influences, limited time, and internal motivational challenges among teenagers.